Karakterisasi Simplisia dan Ekstrak Anti Piretik Daun Dadap Serep (Erythrina Lithosperma Miq) dari Kabupaten Pekalongan - Eko Mugiyanto; S Slamet; Rizki Fatmala (Prosiding University Research Colloquium, 2018)
Quality of compound content in the plant could be influenced bymany factor, it could be the origin of the plant, the body part of theplant being tested, and the character of the extract. Erythrinalithosperma Miq locally known as dadap serep, is a plant thatcommonly spread in the area Pekalongan. The purpose of thisresearch is to identify the character of simplicia and extract fromdadap serep. Characterization using the standardization procedureextract issued by Indonesia National Agency of Drug and FoodControl (BPOM). Characterization was performed on simplicia andethanol 96% extract of leaves. Characterization of simplicia includeorganoleptis, drying shrinkage, water soluble extract, and solubleethanol content. Characterization of ethanol extracts include nonspecificcharacteristics i.e. moisture content, total ash content, andacid soluble ash content. The result of characterization is obtainedappropriate with specification by the range value of each type ofsimplicia parameter and ethanol extract of leaves dadap serepobtained from Pekalongan area.